Improving depression outcomes among Australian primary care patients: protocol for a cluster randomised controlled trial. Issue 2 (10th February 2020) - Carey, Mariko; Sanson-Fisher, Rob; Zwar, Nick; Mazza, Danielle; Meadows, Graham; Piterman, Leon; Waller, Amy; Walsh, Justin; Oldmeadow, Christopher; Deeming, Simon; Searles, Andrew; Henskens, Frans; et al.
Abstract : Introduction: Depression is a common and debilitating condition. In Australia, general practitioners (GPs) are the key providers of depression care. However, available evidence suggests that case finding for depression in primary care is poor. This study will examine whether a systematic approach to screening for depression and assessing patient preferences for depression care improves depression outcomes among primary care patients. Methods and analysis: A cluster randomised controlled design will be used with general practice clinics randomly assigned to either the intervention (n=12) or usual care group (n=12). Patients who are aged 18 and older, presenting for general practice care, will be eligible to participate. Eighty-three participants will be recruited at each clinic. Participants will be asked to complete a baseline survey administered on a touch screen computer at their GP clinic, and then a follow-up survey at 3, 6 and 12 months. Those attending usual care practices will receive standard care. GPs at intervention practices will complete an online Clinical e-Audit, and will be provided with provider and patient-directed resources for depression care. Patients recruited at intervention practices who score 10 or above on the Patient Health Questionnaire-9 will have feedback regarding their depression screening results and preferences for care provided to their GP. The primary analysis will compare the number of cases of depression between the intervention and control groups. Ethics and dissemination: The study has been approved by the University of Newcastle Human Research Ethics Committee, and registered with Human Research Ethics Committees of the University of Wollongong, Monash University and University of New South Wales. Results will be disseminated through peer-reviewed journal publications and conference presentations. Trial registration number: ACTRN12618001139268; Pre-results.